Experimental and numerical evaluation of discharge capacity of sharp-crested triangular plan form weirs. (2017) - Abbaspuor, Bahador; Haghiabi, Amir Hamzeh; Maleki, Abbas; Poodeh, Hassan Torabi
Weirs are those structures used extensively for flood passage, flow measurement, flow deviation and controlling the water level in dams, rivers and open channels. In this study, the numerical model was simulated using flow-3D software and the results from experimental and numerical model were compared. Investigations have shown that the results of RNG turbulence model are better compared to k-ε and LES models. Then, to model the turbulence, and to determine the location of free-surface profile, RNG model and VOF method were used respectively. Experimental results show proper coordination with estimated results of numerical model. For similar low values of h/p, the performance of 30 degree sharp crested triangular plan form weir for discharging of overflow was more suitable than other sharp-crested triangular plan form weirs.